2010
DOI: 10.3844/ajassp.2010.352.359
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body Vibration Exposure to Train Passenger

Abstract: Problem statement: Train is one of the important and famous public transportations in the whole world. High magnitude of whole-body vibration formed by the train may cause diseases and health problems to the human especially a low back pain. This study will give an account of daily exposure to vibration A(8) and Vibration Dose Value (VDV) exposed to the passengers travelling in the train and the effects produced by the exposure towards human body. Approach: One national train travelled from East … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Usually, in vehicles they are drivers, passengers while riding on uneven surfaces and in case of machines they are operators. Also, the human body posture plays an important role in the magnitude of vibration transmission to their body [8]. The WBV usually cause health and safety risk such as; ride discomfort, badly disturb their performance, back pain, shoulder pain, nausea and other health conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, in vehicles they are drivers, passengers while riding on uneven surfaces and in case of machines they are operators. Also, the human body posture plays an important role in the magnitude of vibration transmission to their body [8]. The WBV usually cause health and safety risk such as; ride discomfort, badly disturb their performance, back pain, shoulder pain, nausea and other health conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…The previous study by Ismail et. al (2010) [8] on whole body vibration exposure to train passenger was found that the daily exposure to vibration A(8) from 3 experiment which experiment A are from Kajang to Seremban (0.3221 m/s 2 ), experiment B from Seremban to Gemas (0.2884 m/s 2) , and last is experiment 3 from Seremban to Tampin (0.3749 m/s 2 ) is under exposure action value (0.5m/s 2 ). The result can be categorized as safe exposure to passenger body.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unwanted vibrations due to track irregularities are affecting ride comfort [11]. The passenger is exposed to vibration for long hours, which causes health problems for him, especially low back pain [12], [13]. Many engineering and medical researchers studied the vibration effects on the passenger body and its ability to perform different activities on the train board [14], [12], [15], [16], [17], [18], [19], [20].…”
Section: Introductionmentioning
confidence: 99%